Determination of nurses’ tendency to medical error and the factors affecting this in the Turkish Republic of Northern Cyprus - Nurcan Bilgic; Sibel Altun (Journal of the Pakistan Medical Association, 2022)
Objectives: To determine nurses’ tendency towards malpractice and the factors affecting such a behaviour. Method: The descriptive, cross-sectional study was conducted in October 2018 at four public-sector hospitals in the Turkish Republic of Northern Cyprus, and comprised nurses. Data were collected using the Malpractise Trend Scale in Nursing. Data was analysed using SPSS 21. Results: Of the 236 woman nuses with mean age 39.22±8.32 years, 166(70.3%) were married; 95(40.3%) had bachelor’s degrees; 124(52.5%) worked in internal medicine clinics; 75(31.8%) had been working for >20 years; 86(36.4%) had been working in the same clinics for 1-5 years; and 108(45.7.0%) were working in shifts. The mean Malpractise Trend Scale in Nursing score was 64.62±19.86, indicating low level of tendency. Age, duration of work and shifts had significant association with scale scores (p<0.05) Conclusion: The tendency towards malpractice was found to be low among the nurses in the study, and age, duration of work and shifts were significant factors affecting the tendency. Key Words: Medical error, Malpractise, Nurse, Health safety.